Bossa novas, bikinis, and bad ends - McHugh, Mary (McHugh, Mary. Happy Hoofers mystery, 2016)
The fancy-footed Happy Hoofers--Tina, Janice, Pat, Mary Louise, and Gini-- are kicking off Carnival by entertaining posh guests at the most elegant hotel in Rio de Janeiro. Stunning beaches and spectacular views abound. But the party is cut short for the fab five when their alluring Brazilian companion is found dead in her room, without a clue as to what killed her.